Bone histological correlates for air sacs and their implications for understanding the origin of the dinosaurian respiratory system. (3rd January 2018) - Lambertz, Markus; Bertozzo, Filippo; Sander, P. Martin
Abstract : Air sacs are an important component of the avian respiratory system, and corresponding structures also were crucial for the evolution of sauropod dinosaur gigantism. Inferring the presence of air sacs in fossils so far is restricted to bones preserving internal pneumatic cavities and foramina as osteological correlates. We here present bone histological correlates for air sacs as a new potential identification tool for these elements of the respiratory system. The analysis of several avian and non-avian dinosaur samples revealed delicate fibres in secondary trabecular and secondary endosteal bone that in the former case (birds) is known or in the latter (non-avian dinosaurs) assumed to have been in contact with air sacs, respectively. The bone histology of this 'pneumosteal tissue' is markedly different from those regions where muscles attached presenting classical Sharpey's fibres. The pneumatized bones of several non-dinosaurian taxa do not exhibit the characteristics of this 'pneumosteum'. Our new histology-based approach thus can be instrumental in reconstructing the origin of air sacs among dinosaurs and hence for our understanding of this remarkable evolutionary novelty of the respiratory system.